A New Era of Education: Exploring Teachers' Perspectives on the Utilization of ICT-Based Learning Resources in Schools - Budiarto, Mochamad Kamil; Rahman, Abdul (Journal of Teaching and Learning, 2025)
In the digital revolution era, the role of teachers in utilizing ICT-based learning resources in schools has become very important. However, the utilization of ICT that is not optimal has been identified, which often occurs in some schools in developing countries, possibly because of factors such as human resources readiness, facilities, and regulations inherent in each educational institution. This research aims to describe teachers’ perspectives on ICT learning resources that have been used for the learning process. This research is a qualitative study with a case study type, involving a sample of 7 teachers at the high school level in Central Java and West Java. Data collection techniques include semi-structured interviews, followed by an interview guide as the data collection instrument. As for an interview, it was analyzed thematically to describe an overview of the issues commonly raised by teachers during the data collection process.The research results show that there are 3 themes that are often the main topics of discussion, namely motivation and readiness of teachers in utilizing ICT-based learning resources, teachers’ perspectives and resource support the implementation of ICT-based learning resources, and the challenges that teachers face when implementing ICT-based learning in the classroom. The results of this research have the potential to assist in the professional development of teachers in integrating ICT to embrace dynamic and innovative learning in the digital era.